Answering Reading Texts on English Tryout Test Based on the 12th Grade Students' Strategies at SMA Negeri 1 Kuripan Lombok Barat - Lail, Husnul (JOLLT Journal of Languages and Language Teaching, 2020)
The purpose of this study was to find out the answering reading text on English Tryout Test based on the 12th Grade students' Strategies at SMA Negeri1 Kuripan Lombok Barat in the Academic Year of 2018/2019. The population was 329 students and the sample was XII. A class that consists of 31 students were involved in this study. This study was designed as a descriptive study in analyzing the data. The data was obtained through the questionnaire.Â  It was to find out which was the mostly strategies used by students among meta-cognitive and cognitive strategies. The result of this study showed that there were two kinds of strategy used by the students: meta-cognitive (80.31%) and cognitive (89.37%) strategies. Moreover, the most dominant meta-cognitive strategies used by students were; setting plans on how to complete the test, aware of the objective of the reading tasks, correct mistakes immediately, and checking the answers of reading tasks carefully before submitting the test. While the most dominant cognitive strategies used by the students were: guessing, scanning, and skimming. The reason why guessing, scanning, and skimming get the highest percentage and being the most dominant strategies chosen was that they were very easy and simple strategies to apply when facing such a reading text. They did not need much time to identify the text. In addition, the reason guessing also got a high percentage because it was the most effective way to use during the test by using a dictionary was not allowed.